ANALISIS KEMAMPUAN PEMECAHAN MASALAH SOAL HOTS PADA MATERI BARISAN DAN DERET SISWA KELAS XI SMA NEGERI 1 BARUMUN TENGAH - Tanjung, Renni Juwita; Adinda, Anita (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to analyze the mathematical problem-solving abilities of 25 eleventh-gradestudents at SMA Negeri 1 Barumun Tengah in solving Higher Order Thinking Skills (HOTS)questions related to arithmetic and geometric sequences. The research employed a descriptivequalitative approach with data collected through written tests, interviews, and observations. Thefindings indicate that most students struggled to solve HOTS questions systematically. Based onPolya’s problem-solving steps, 80% of students were able to understand the problem, 60% coulddevise a strategy, 52% were able to carry out the strategy, and only 36% evaluated their resultsindependently. The greatest difficulties were found in the planning and evaluation stages, primarilydue to low critical thinking skills, lack of exposure to contextual questions, and the dominance ofprocedural-based teaching. These findings highlight the importance of systematically integratingHOTS questions into mathematics instruction to foster students’ higher-order thinking skills.